The Effect of Return on Asset and Operating Income on the Level of Profit Sharing from Mudharabah Deposits at BMT UGT Nusantara Capem Jajag in the Period 2019-2023 - Eka Febriani; Nur Anim Jauhariyah; Edy Sujoko (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of Return On Assets and Operating Costs Operating Income on the level of profit sharing of mudharabah deposits at BMT UGT Nusantara Capem Jajag during the period 2019-2023. The research method used is a quantitative method by analyzing secondary data from financial reports for 60 months in 2019-2023, with independent variables consisting of ROA and BOPO, while profit sharing of mudharabah deposits is the dependent variable. Data analysis uses multiple linear regression analysis tests with SPSS software. The results of the study indicate that Return On Assets has a significant effect on profit sharing of mudharabah deposits with a positive t-count value, while Operating Costs and Operating Income have a significant effect on profit sharing of mudharabah deposits with a negative t-count value. The amount of contribution of Return On Assets and Operating Costs Operating Income to the level of profit sharing of mudharabah deposits at BMT UGT Nusantara Capem Jajag during the period 2019-2023 is 77.8%.